Migration and FDI: Reconciling the standard trade theory with empirical evidence - Hubert Jayet; Léa Marchal (Kiel Institute for the World Economy (IfW), 2016)
This article focuses on an apparent conflict between the standard trade theory and available empirical evidence on factor flows. Theoretically, labor and capital flows must be substitutes. However, empirical papers find migration and FDI to be either substitutes or complements, depending upon the skill content of migration. To reconcile the standard theory with these empirical results, we develop a two-country general equilibrium model. We consider three factors - capital, unskilled and skilled labor - and two internationally traded goods. Countries only differ in their factor endowments. The first country is a developing country amply endowed with unskilled labor; the second one is a developed country well endowed with skilled labor. Under imperfect factor mobility, we find that capital and unskilled labor flows are substitutes, while capital and skilled labor flows are complements.
Keywords: F11; F21; F22; J61; 330; Capital flows; Migration; Skills; Standard trade theory